2024
DOI: 10.3390/su16020707
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Green Space on University Students’ Mental Health: The Mediating Roles of Solitude Competence and Perceptual Restoration

Jun Zhang,
Jinghua Jin,
Yimeng Liang

Abstract: With the prevalence of mental health problems among college students, perceptual recovery and the sensory dimensions of perception (PSD) have emerged as crucial environment-related factors for psychological well-being. However, there has been relatively limited research on how these factors directly and indirectly impact the restoration experience of college students in green spaces on campuses. Therefore, the aim of this study was to determine the influence of college students’ intrinsic motivation on their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Although nature and green spaces have many positive effects on people, existing studies have also demonstrated that exposure to campus green spaces has a positive impact on student's mental health and that green environments on campus can significantly enhance students' mental health and help them recover from stress and mental fatigue [14]. However, college students' heavy schedules, coursework, and extracurricular work may cause them to spend most of their time indoors, needing more physical activity and preventing easy and frequent access to green spaces on campus [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although nature and green spaces have many positive effects on people, existing studies have also demonstrated that exposure to campus green spaces has a positive impact on student's mental health and that green environments on campus can significantly enhance students' mental health and help them recover from stress and mental fatigue [14]. However, college students' heavy schedules, coursework, and extracurricular work may cause them to spend most of their time indoors, needing more physical activity and preventing easy and frequent access to green spaces on campus [15].…”
Section: Introductionmentioning
confidence: 99%